Comparison of Centralized and Distributed Provisioning of Lightpaths in Mesh Restored Optical Networks - Ramamurthy, Ravi; Sengupta, Sudipta; Chaudhuri, Surajit (Optical Fiber Communication (OFC) Conference, Anaheim (USA), 2001)
This paper compares centralized and distributed online provisioning approaches in optical networks. In the centralized approach, complete network state is available for path computation. In the distributed approach, summarized information is available for path computation.